Do International Business Students Who Are Studying in Australia Have Similar Academic Outcomes? A Comparison of Undergraduate and Postgraduate Students - Stenberg, Luz Centeno (Journal of Education and Training, 2023)
The paper explores the characteristics of business students studying in Australia. A total of 1907 students (1033 undergraduate and 874 postgraduate students) are included in the study between 2012 and 2016. These students are either from a higher education (tertiary) private provider of undergraduate business courses or from one of the Australian universities studying at the postgraduate level. The paper attempts to examine if there are similarities in undergraduate and postgraduate business student outcomes that could be attributed to country of origin and gender. The paper argues that the human capital pursuit among international business students studying in Australia is similar due to the linkages between immigration, labor market and education policies. These linkages might have facilitated the perceived risk-return relationship of studying in Australia and as a result led to attracting similar (international) students studying at the undergraduate and postgraduate levels. Ordinary least squares (OLS) models’ results suggest that gender and country of origin are important in predicting success. In particular, being female is positively related to academic success and certain student groups dominate the international students’ landscape in Australia.